Critical Social Science in Sport Management Research: A Scoping Review - Bodin, Kerri; Teare, Georgia; Taks, Marijke (Frontiers in Sports and Active Living, 2022)
Sport management scholars have called for the application of broader research approaches, including critical social science. Such approaches help uncover the less-desirable aspects of sport and, therefore, offer a basis for positive change. While there have been advancements in the use of innovative research approaches over time, there remains little understanding of how these calls have been addressed. The purpose of this scoping review is to examine trends, gaps, and the use of critical social science and associated approaches in sport management scholarship. Two hundred sixteen relevant articles were identified through a database search (i.e., five platforms), complemented with a manual search of 419 journals. Results indicate that an increase in critical research published in sport management journals was evident following 2005. Findings suggest that there remains space for increased publication of critical social science work in sport management journals and for researchers to better articulate their research approaches in scholarly outputs.